Socio-Economic Impact of Covid-19 Pandemic and Its Implication on Education - Benryl Bacaro Llamera (International Journal of Qualitative Research, 2021)
This study contributes to the Covid-19 literature by understanding the recent pandemic implications on seaweed farmers' lives. The study's respondents are tripartite, composing seaweed farmers, students, and significant personnel from the Local Government Units (LGUs). Data were collected through face-to-face interviews with strict adherence to the IATF’s minimum health standards. Gathered data were analyzed thematically. Results show that the pandemic impacted seaweed farmers’ lives socially and economically. The pandemic has implications for the education of the children of the seaweed farmers as it is gleaned in the findings that most of them struggle over the new modes of learning. However, the implications were mainly domino effects of the adverse impacts of the pandemic on the parents. The study’s findings are substantial in mitigating the ongoing pandemic’s adverse effects and laid a foundation for the proposed intervention framework model. Conclusions were discussed and gave light to recommendations primarily offered to the Local Government Units (LGUs), educational institutions under the Department of Education Agutaya District, and concerned higher education institutions in the Province of Palawan as a basis for policy and program formulations aimed at mitigating the effects of the Covid-19 pandemic on the lives of seaweed farmers in Agutaya, Palawan.